Glimpses of Sustainability in Perth, Western Australia: Capturing and Communicating the Adaptive Capacity of Activist Groups - Dhakai, Subas P (Consilience, 2014)
The root causes of unsustainability e.g. social and environmental injustice are often associated with the failure of the state or the market, and community based activism is one of the ways societies have responded to tackle the sustainability conundrum. Millions of sustainability activist groups (SAGs) are actively engaged in various social and environmental initiatives around the world. While the potential of visualisation to foster sustainability causes has been increasingly utilised, photographic narratives on adaptive capacity – the ability to secure various forms of necessary resources in changing circumstances – of SAGs have been under-represented. This paper responds to this gap and captures the glimpses of one of the longest running activisms in Perth, the state capital of Western Australia.